2022
DOI: 10.15252/embr.202255472
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK‐dependent phosphorylation of TFEB promotes monocyte‐to‐macrophage differentiation

Abstract: The transcription factor EB (TFEB) regulates energy homeostasis and cellular response to a wide variety of stress conditions, including nutrient deprivation, oxidative stress, organelle damage, and pathogens. Here we identify S401 as a novel phosphorylation site within the TFEB proline-rich domain. Phosphorylation of S401 increases significantly in response to oxidative stress, UVC light, growth factors, and LPS, whereas this increase is prevented by p38 MAPK inhibition or depletion, revealing a new role for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…However, this may also reflect biological differences between primary cells and the cell line. Previous work suggested that TFEB was required for human THP-1 cell differentiation induced by PMA (97); in contrast, we did not detect a defect in BMDM differentiation in Tfeb -deleted murine cells. Furthermore, we previously showed that PMA activates TFEB via protein kinase D1 (66).…”
Section: Discussioncontrasting
confidence: 99%
“…However, this may also reflect biological differences between primary cells and the cell line. Previous work suggested that TFEB was required for human THP-1 cell differentiation induced by PMA (97); in contrast, we did not detect a defect in BMDM differentiation in Tfeb -deleted murine cells. Furthermore, we previously showed that PMA activates TFEB via protein kinase D1 (66).…”
Section: Discussioncontrasting
confidence: 99%
“…3e). Previous work has shown that TFEB levels are reduced by treatment with lipopolysaccharide (LPS), a stress inducer that causes the activation of inflammatory responses in various cell types 21, 58 . Immunoblot analyses showed that LPS treatment indeed reduced the levels of WT TFEB in a dose-dependent manner; however, it had a lesser impact on TFEB-6xA levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TFEB plays a pivotal role in the regulation of lysosome-to-nucleus communication by translating inputs from mechanistic target of rapamycin complex 1 (mTORC1) [9][10][11][12][13] and other key metabolic regulators including protein kinase B (PKB/AKT) 14,15 and adenosine monophosphate-activated protein kinase (AMPK) 16 , all of which have specific roles at the lysosome [17][18][19] . Importantly, these and other kinases modify TFEB on distinct subsets of amino acids [9][10][11][12][13][14][15][16][20][21][22][23] , indicating that TFEB has several independent layers of regulation that presumably execute different branches of the cellular adaptive response or serve additional functions. Studies with cultured cells have shown that, in normal cell growth conditions, TFEB protein is predominantly found in the cytosol in an inactive state.…”
Section: Introductionmentioning
confidence: 99%
“… 52 , 53 The p38 MAPK pathway also plays a central role in the regulation of monocyte/macrophage development and differentiation. 54 57 To validate the mechanism of Tim4-regulated CD301b + macrophages phenotype, we focused on p38 MAPK signaling pathway because evidences have described that Tim4 in macrophages could mediate p38 MAPK signaling pathway and might facilitate tissue regeneration. 34 , 35 The results indicate that Tim4-mediated p38 MAPK signaling pathway was responsible for modulating phenotypic differentiation of macrophages into CD301b + macrophages.…”
Section: Discussionmentioning
confidence: 99%